Law on obligations and contracts : notes and cases - Samson, Anna Rhea Valle (Quezon City, Philippines : C & E Publishing Inc., 2016)
Written for college undergraduates taking up a course on obligations and contracts, Law on Obligations and Contracts: Notes and Cases discusses the basic laws and legal concepts related to the sources, nature, effects and extinguishment of obligations as well as the essential requisites, forms and interpretation of contracts. The material expains the elements of numerous codal provisions to enable students to analyze the law and cites real-life cases to illustrate key doctrines. Practical end-of-chapter exercises are also provided to develop critical thinking and analytical skills which are necessary in resolving legal issues and assessing the students' comprehension of the lessons.
Title I. Obligations -- Title II. Contracts.
Includes index.
Keywords: OBLIGATION (LAW) -- PHILIPPINES